Marked Seasonal Changes in the Microbial Production, Community Composition, and Biogeochemistry of Glacial Snowpack Ecosystems in the Maritime Antarctic. Issue 7 (15th July 2021) - Hodson, A. J.; Sabacka, M.; Dayal, A.; Edwards, A.; Cook, J.; Convey, P.; Redeker, K.; Pearce, D. A.
Abstract: We describe seasonal changes in the biogeochemistry, microbial community and ecosystem production of two glacial snowpacks in the maritime Antarctic during a cold summer. Frequent snowfall and low, intermittent melt on the glaciers suppressed surface photosynthesis and promoted net heterotrophy. Concentrations of autotrophic cells (algae and cyanobacteria) were therefore low (average: 150–500 cells mL −1 ), and short‐term estimates of primary production were almost negligible in early summer (<0.1 μg C L −1 d −1 ). However, order of magnitude increases in Chlorophyll a concentrations occurred later, especially within the mid‐snowpack and ice layers below. Short‐term primary production increased to ca. 1 μg C L −1 d −1 in mid‐summer, and reached 53.1 μg C L −1 d −1 in a mid‐snow layer close to an active penguin colony. However, there were significantly more bacteria than autotrophs in the snow (typically 10 3 cells mL −1, but >10 4 cells mL −1 in basal ice near the penguin colony). The ratio of bacteria to autotrophs also increased throughout the summer, and short‐term bacterial production rates (0.2–2000 μg C L −1 d −1 ) usually exceeded primary production, especially in basal ice (10–1400 μg C L −1 d −1 ). The basal ice represented the least diverse but most productive habitat, and a striking feature was its low pH (down to 3.3). Furthermore, all of the overlying snow cover became increasingly acidic as the summer season progressed, which is attributed to enhanced emissions from wet guano in the penguin colony. The study demonstrates that active microbial communities can be expected, even when snowmelt is intermittent in the Antarctic summer. Plain Language Summary: We consider the importance of snow as one of Antarctica's most important land‐based ecosystems by describing snowpack ecosystem behavior at two sites upon a small maritime Antarctic ice cap. We show that a strong seasonal increase in the number of bacteria and snow algae occurs during the summer, despite the fact that our study coincided with a cold summer with frequent, wet snowfall events. These kept burying the snow algae, making photosynthesis difficult and allowing the bacterial community to dominate. An unexpected consequence was that the conditions also enhanced the decomposition of wet penguin guano, resulting in the release of organic acids whose subsequent deposition resulted in very acidic conditions within the snow matrix. Warmer summers with less snowfall will therefore experience completely different biological and chemical conditions in the snow habitat, emphasizing the climate sensitivity of this ice‐hosted ecosystem. Key Points: Regional nutrient enrichment by marine fauna influences the microbial ecology of glacial snowpacks in the maritime Antarctic during summer Cold summers with low melt and frequent snowfall reduce photosynthesis at the surface and allow bacterial production to dominate Persistent moisture supply to penguin guano enhances the effects of ammonium and organic acid deposition onto the snow ecosystem